Membangun Jembatan Menuju Keberhasilan Literasi Dan Numerasi Melalui Program Kampus MengajarDi Sdn Klampis Ngasem Ii/511 Surabaya:Peran Sentral Perpustakaan Sekolah - Retno Ayu Widyastuti; Cholis Hidayati (Jurnal Pendidikan dan Sastra Inggris, 2023)
Literacy and numeracy are important aspects of education that play a key role in shaping students' knowledge and skills. Literacy includes the ability to read, write and speak, while numeracy involves understanding mathematical concepts and applying them in everyday life. Mastery of these skills provides students with a solid foundation, encouraging critical thinking, analytical skills, and effective communication. Through the Teaching Campus program, which aims to improve the literacy and numeracy of Indonesian students, tertiary students work closely with teachers and schools to develop teaching models that are innovative and inspire creativity. This program creates opportunities for people to contribute to improving the quality of student education through community service in schools. At SDN Klampis Ngasem II/511 Surabaya, the program implements the "Reading Veranda" initiative as a temporary solution to overcome the shortage of library space. This initiative ensures students' access to adequate reading materials and creates an engaging learning environment outdoors. The Veranda Baca program has had a positive impact in improving students' literacy and numeracy while creating a stimulating and innovative learning environment.